Determination of Total Flavonoid Content and Antioxidant Activity of Avocado Stem Bark (Persea americana Mill) Ethanol Extract in Inhibiting DPPH - Risnata, Richa Poetri; Hidayati, Agriana Rosmalina (Jurnal Biologi Tropis, 2024)
Excessive free radicals in the body can trigger degenerative diseases. Therefore, antioxidant help is needed from outside the body to inhibit free radicals. Long-term use of synthetic antioxidants is limited because they can cause cancer. This encourages the development of natural antioxidants, one of which comes from avocado stem bark. Avocado stem bark contains flavonoids which act as antioxidants. This study aims to determine the total flavonoid content and antioxidant activity of avocado stem bark ethanol extract in inhibiting DPPH. Avocado stem bark was extracted using sonication followed by the identification of flavonoids using a tube test and thin layer chromatography test. Determination of total flavonoid content was carried out using the colorimetric method and antioxidant testing using the DPPH method. The results obtained were that the avocado stem bark was positive for containing flavonoids based on tube tests and thin layer chromatography. The results of determining the flavonoid content in the ethanol extract of avocado stem bark were 5.572 mgQE/g. The ethanol extract of avocado stem bark is a very strong antioxidant with an IC50 of 21.221 ppm. So it was concluded that avocado stem bark can be used as a natural antioxidant candidate.